The Function THE FUNCTION OF GUAL SURUNG DAYUNG IN SIMALUNGUN COMUNTY NORTH SUMATERA: THE FUNCTION OF GUAL SURUNG DAYUNG IN SIMALUNGUN COMUNTY NORTH SUMATERA - Hirza, Herna; Astri Elife Saragih (Program Studi Pendidikan Musik, 2025)
This study aims to determine the function of Gual Surung Dayung in Simalungun Comunity- North Sumatera. The method used in this study uses a descriptive qualitative method. Data collection techniques used in this study were observation, interviews and documentation. The results of this study indicate that the function of Gual Surung Dayung in the Marilah Art Studio, Raya District, Simalungun Regency consists of; 1) Function as a mood expression, 2) Function as a means of entertainment, 3) Function as a means of communication, 4) Function as a physical response, 5) Function of protecting adherence to social norms.